Philobota sp (Lepidoptera Oecophoridae) a potential new pasture pest in New Zealand - Popay, A.J.; Gunawardana, D. (New Zealand Plant Protection, 2011)
In February 2010 caterpillars initially identified as a species of Philobota (Lepidoptera Oecophoridae) were found in a nursery area at Ruakura Research Centre in Hamilton The identification was confirmed by MAFs Plant Health and Environment Laboratory (PHEL) This genus is endemic to Australia where over 400 species are known a few of which are regarded as minor pests of pasture A survey of the Ruakura site found Philobota in three other areas two of which bordered urban areas It was found infesting perennial ryegrass and tall fescue trials in two parts of the campus and in pasture areas in the other two locations suggesting this insect is primarily a grass feeder It is highly likely Philobota is not confined to Ruakura and there is no evidence that the infestation originated at this site Although few live caterpillars could be found by August 2010 observations in 2011 suggest populations have multiplied in at least one trial site Commonly called the pasture tunnel moth this insect is univoltine and weaves characteristic tunnels from grass and debris with chimneys that protrude above ground Caterpillars reared at PHEL yielded only female moths which have been tentatively identified as Philobota nr pilipes